Does the Addition of Cetuximab to Radiochemotherapy Improve Outcome of Patients with Locally Advanced Rectal Cancer? Long-Term Results from Phase II Trials - M. Kripp; K. Horisberger; S. Mai; P. Kienle; T. Gaiser; S. Post; F. Wenz; K. Merx; R.-D. Hofheinz (Gastroenterology Research and Practice)
Purpose. The addition of cetuximab to radiochemotherapy (RCT) failed to improve complete response rates in locally advanced rectal cancer (LARC). We report the long-term results in patients treated within two sequential clinical trials. Methods. Patients receiving neoadjuvant RCT using capecitabine and irinotecan (CapIri) within a phase I/II trial or CapIri + cetuximab within a phase II trial were evaluated for analysis of disease-free survival (DFS) and overall survival (OS). KRAS exon 2 mutational status had been analyzed in patients receiving cetuximab. Results. 37 patients from the CapIri trial and 49 patients from the CapIri-cetuximab treatment group were evaluable. Median follow-up time was 75.2 months. The 5-year DFS rate was 82% (CapIri) and 79% (CapIri-cetuximab) (P=0.62). The median OS was 127.4 months. 5-year OS was 73% for both groups (CapIri and CapIri-cetuximab) (P=0.61). No significant difference in DFS (P=0.86) or OS (P=0.39) was noticed between patients receiving CapIri and those receiving CapIri-cetuximab with KRAS wild-type tumors. Conclusions. As the addition of cetuximab did not improve neither DFS nor OS it should not play a role in the perioperative treatment of patients with LARC, not even of patients with (K)RAS WT tumors.